What is it like to be a fur-parent? / Dr. Leow Min Hui - Leow, Min Hui (Academy of Language Studies, 2023)
Giving care to a pet is like giving care to a human child. Someone would say taking a role as a fur parent before becoming a real parent is a good practise that nurtures motherly love. Well, I did not give much thought when I first brought Lucky home. It was simply “Aw! My childhood’s dream finally comes true! I have got myself a pet dog!” Up until the first week after I brought a puppy home, that was a nightmare! It was 7 years ago, and Lucky was still a 3-month-old puppy. He (I prefer to call my fur baby “he” instead of “it”) is a Jack Russell Terrier with intense curiosity and adventurous nature. He is a great escape artist who can climb, jump, or dig under the cage. Imagine that you are walking up to your front door and finding an escaping puppy pooped all over himself, pee all over the place, and your USB cable was badly chewed. What are you going to do? The naive puppy would wag his tail and give you a friendly greeting as usual, unaware that he had done something wrong. You must bear in mind that at that point, it would be pointless to scold or punish him because he would not understand the reason and would likely have forgotten what he had done.